Simultaneous interpretation in interpreter-mediated remote legal proceedings: some observations from a forum theatre study - Huws, Catrin Fflûr; Jewell, Rhianedd; Binks, Hanna; Shafto-Humphries, Non S; Schwede, Leo (Comparative Legilinguistics, 2024)
This article concerns the findings of a study into participant responses to remote interpreter-mediated court proceedings using Welsh-English simultaneous interpretation. The study employs the forum theatre techniques of Augusto Boal, to explore how counsel, witnesses, mock-jurors and interpreters participate in hearings conducted remotely. The study was conducted in 2022, when the early difficulties of conducting hearings remotely because of the Covid pandemic had been resolved, and legal systems were considering how remote hearings could operate in the future.